Pengembangan Video Pembelajaran IPA Dalam Upaya Meningkatkan Pemahaman Pergerakan Tata Surya Siswa Kelas VI SDN Cibeber - Nusrodiah Lubis; Yayat Ruhiyat; Isti Rusdiyani (Universitas Mathla'ul Anwar Banten, 2022)
Development of A Science Learning Video in An Effort to Improve Understanding of The Movement of The Solar System for Sixth Grade Students at SDN Cibeber District, Cilegon City. This study uses the Research and Development(Researchand Development / R & D) in the form of quantitative and qualitative data. Qualitative data are the results of feasibility tests by material experts, media experts, and audiences. development model that can be used, one of which is thedevelopment model ADDIE (Analyze-Design-Development-Implementation-Evaluation)This study aims to (1) produce video-based learning media products for science subjects, the subject of the movement of the solar system at SDN Cibeber City Cilegon. (2) Analyze and describe the validity of the use of video-based learning media in improving students' understanding of the material for the movement of the solar system at SDN Cibeber District, Cilegon City (3) Analyzing and describing the feasibility of using video-based learning media in improving students' understanding of movement material. solar system at SDN Cibeber District, Cilegon City. The results of this study show (1) the Eligibility Data of Media Experts Based on the results of the assessment of media experts with a total score of 81% which in the table includes the Very Eligible category to be tested on students. (2) The results of the Feasibility Data of the Material Experts Based on the results of the assessment of the material experts with a total score of 83% which in the table belongs to the category of Very Eligible to be tested on students (3) The results of the Feasibility Data from the respondents' assessments are based on the results of the assessments of 24 grade VI students with the total score is 1840, while the expected score is 2400, then the percentage of eligibility is calculated using the Eligibility Percentage formula. So the results of the feasibility of learning media according to the respondents are 82.08 which in the table is included in the very capable category.